THE ROLE OF THE CULTURAL AND INFORMATION APPROACH IN THE FORMATION OF THE UNIVERSAL CULTURE OF SCHOOLCHILDREN - Yuldoshev Utkir Zhumakuzievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the problem of cultural and information approaches to the formation of information cultures of schoolchildren in the conditions of globalization and digitalization of education